Social Imaginaries of Tourists at the Ruins of Armero, Tolima - Mora Forero, Jorge Alexander (2023)
Armero is a municipality located in the department of Tolima, marked by the disaster that occurred on November 13, 1985. This research focuses on investigating why tourists choose to visit the municipality and their thoughts on dark tourism. Therefore, the objective is to analyze the social imaginaries and the tourist’s perception in a place mourning events that resulted in the death of more than 25,000 people and other incalculable damages. The methodology is qualitative and descriptive, using surveys as the technique. Simple sampling identifies 49 participants who, after touring the ruins of Armero, are questioned about their interest, feelings about the place, and empathy with the locals. It is concluded that dark tourism in Colombia, particularly in sites where catastrophic events occurred, can serve as a gateway to explore this type of tourism, as many countries already do.